CONSUMPTION AND LEISURE COMMUTING ON THE HINTERLAND OF PRESIDENTE PRUDENTE-SP - Engel, Priscila Estevam [UNESP]; Whitacker, Arthur Magon [UNESP] (Univ Estado Rio Janeiro, 2017)
Like nodes of the urban network, the apprehension of the relationship between the middle city and the urban centers of its hinterland is of utmost importance, as its consumer market is also made by the neighbor population that incurs commuting generated by the opportunity or need for consumer goods and services. In this paper we are dedicated to construe results surveys in four cities of the 10th Administrative Region of Presidente Prudente that will help us, in the context of the Brazilian urban network, to analyze and compare the interurban centrality of the middle city of Presidente Prudente, located in the west of Sao Paulo State. This methodological procedure contributes to the study of commuting, scaling and analyzing the shifts that have Presidente Prudente as a destination and to identify the main reasons for the commuting to consumption of goods and services in shopping malls.
Keywords: Middle Cities; Shopping Centers; Commuting; Consumption